Availability and affordability of essential medicines for non-communicable disease management in primary healthcare: Evidence from three municipalities in Ghana - Mary Yeboah; Richard Abeiku Bonney; Loretta Adu-Boahemaa Antwi; Pius Amponsah Anane; Obed Kwabena Offe Amponsah; Peter Agyei-Baffour (PLoS ONE, 2026)
Background Non-communicable diseases (NCDs) cause 74% of global deaths, disproportionately affecting LMICs like Ghana. Chronic treatment remains hindered by medicine shortages and high costs, consuming over 50% of the minimum wage incomes. Despite Ghana’s NCD policies, supply chain gaps and price inflation persist. This study assesses access to medicine, operationally defined as availability and affordability, in three municipalities to inform reforms for Universal Health Coverage and achieve SDG 3.4 targets. Methods This cross-sectional mixed study assessed the availability and affordability of NCD medicines in three municipalities in Ghana using WHO/HAI methods. Data on 62 medicines were collected from nine health facilities, supplemented by interviews with pharmacy managers. Results This study assessed access to NCD medicines across three municipalities in Ghana, revealing stark disparities. Availability varied significantly by location (Oforikrom 70% vs. Juaben 48.6%, p < 0.001) and facility type (government 67.2% vs. private 54.6%, p = 0.042). Insulin was least affordable (3.94–8.74 days’ wages), with 10-fold metformin price differences between municipalities. Private facilities charged 2–5 × more than the government for chronic medications. Logistic regression analysis showed that patients in private facilities were significantly more likely to encounter unaffordable NCD medicines compared to those in public facilities (AOR = 3.85, p = 0.001). Supply chain delays (2–3 weeks) and National Health Insurance Scheme (NHIS) reimbursement delays exacerbated gaps. Conclusion This study highlights inequities in access to NCD medicines in Ghana, with stark gaps in availability and affordability, especially in underserved areas. Findings reveal high costs, stock-outs, and geographic disparities as key factors, underscoring the need for supply chain reforms, price regulation, and municipal oversight to advance equitable, sustainable, universal health coverage.